Analisis Yuridis Perjanjian bagi Hasil Perpecahan Lahan Pertanian di Desa Dengkol Kabupaten Malang - Ayu Sekar Gayatri; Risky Febria Nurita; Mohammad Fahrial Amrulla (University of Merdeka Malang, 2023)
This scientific paper analyzes the juridical analysis of profit-sharing agreements on split land in Dengkol Village, Malang Regency. The legal issue to be analyzed is a land dispute case in Malang Regency. The purpose of this research is to reach an agreement on land disputes that benefit both parties, namely between the Air Force and the Community and to find out the problems that occur and result in land disputes. This study uses a normative legal research method based on a study of cases and laws and regulations. The land dispute that occurred in Malang Regency was proven to have occurred due to incitement carried out by the local village head who was assisted by irresponsible persons, in this case it was also resolved in a non-litigation manner which was carried out outside the court and carried out by mediation.